Comparative Analysis of the particle size on the porosity and the tensile properties of aluminium based metal matrix nano-composites. (2021) - Ghanaraja, S.; Ray, Subrata; Nath, S.K.
Abstract: Milling a mixture of aluminium and manganese dioxide (MnO2 ) powders mixed in ratio of 1:7 by weight and the particle size has been varied by milling in a vibratory disc mill for 450, 600 and 750 min at 700 rpm to obtain Nano-sized alumina particles. Melting commercially pure aluminium followed by addition of different duration of milled powder mix while stirring the melt to synthesis nano-composites. The remaining aluminium powder will melt when the powder mixture will be added to molten Al-Mg alloy during composite processing. The remaining manganese oxide will also react with molten Al-Mg alloy during solidification processing of composite and generate alumina particles (in-situ). The reaction between manganese dioxide and molten alloy releases manganese for alloying with the molten Al-Mg alloy. To enhance wetting of resulting alumina particles by the melt, magnesium is added. It is observed that the porosity in the cast composite increases with increasing addition of particles milled for a given time and it is interesting to observe that for the same amount of addition, powders milled for higher milling time cause higher porosity. There is increasing strength and ductility compared with base alloy and composite prepared with 2wt% addition of different duration milled powder. The tensile properties for AM alloy shows yield strength of 75.9 MPa, tensile strength of 169.8 MPa and elongation of 11.12%. Tensile properties of different composites for addition of 2 wt% powder mix milled for 450, 600 and 750 min shows that 113.3 MPa, 91.8 MPa and 77.3 MPa of yield strength respectively, 250 MPa, 225.2 MPa and 216.8 MPa of tensile strength respectively and 25.65%, 25.68% and 23.91% of elongation respectively. For addition of 2 wt% powder mix milled for 450 min, there is improvement in yield strength by about 25%, tensile strength by about 35% and ductility by more than 120% in the nano-composite over those observed in the base alloy.